Factors influencing the decision to attend screening for cancer in the UK: a meta-ethnography of qualitative research - Young, Ben; Bedford, Laura; Kendrick, Denise; Vedhara, Kavita; Robertson, John; das Nair, Roshan (Oxford University Press, 2017)
Background: This review aimed to better understand experiences of being invited to cancer screening and associated decision-making. Methods: Qualitative evidence explaining UK cancer screening attendance decisions was systematically identified. Data were extracted and meta-ethnography used to identify shared themes, synthesise findings and generate higher level interpretations. Results: Thirty four studies met inclusion criteria. They related to uptake of breast, cervical, colorectal, prostate, ovarian and lung cancer screening. Three primary themes emerged from the synthesis. Relationships with the health service shaped decisions, influenced by trust, compliance with power, resistance to control or surveillance, and perceived failures to meet cultural, religious and language needs. Fear of cancer screening was both a motivator and barrier in different ways and to varying degrees. Strategies to negotiate moderate fear levels were evident. Experiences of risk included the creation of alternative personal risk discourses and the use of screening as a coping strategy, influenced by disease beliefs and feelings of health and wellness. Conclusions: The findings highlight the importance of the provider-patient relationship in screening uptake and enrich our understanding of how fear and risk are experienced and negotiated. This knowledge can help promote uptake and improve the effectiveness of cancer screening.